Rejection of copper from aqueous solution using rice hull ash/clay ceramic membrane - Putheavy, Tim (2010)
The study investigated the application of ceramic membrane made from rice hull ash mixed with clay to remove copper from aqueous wastewater. The operating variables studies were feed concentration of 100-600 ppm (typical concentration in metal plating wastewater), pressure of 10-30 psi, fed flowrate of 1-2 L/min and pH of 3-9. It is observed that the rejection of copper varies from 59 to 99.9%. The lowest rejection of copper was observed when the initial feed concentration, pressure, pH and feed flowrate were 200 ppm, 30 psi, 5 and 2 L/min. The highest rejection of the metal was achieved at initial feed concentration of 100 ppm, pressure 30psi, feed flowrate 2 L/min in basic solution of pH 9. Highest copper rejection was achieved nearly 100% this is because of increasing negative charges on the surface of the membrane in higher pH and precipitation of copper oxide and hydroxide. Thus, the performance maybe attributed to both sieving by the membrane and precipitation. At the condition of low feed concentration of 100 ppm, pressure 30 psi, high feed flowrate 2 L/min and pH 4, precipitation was not observed and performance of the membrane without precipitation of copper occurrence was found to be the best.